Extraction of biological hydroxyapatite from tuna fish bone for biomedical applications - LATIF, A.F.A.; Mohd Pu’ad, N.A.S.; RAMLI, N.A.A; MUHAMAD, M.S; Abdullah, H.Z.; IDRIS, M.I.; Lee, T. C. (2020)
Natural hydroxyapatite (HAp) is known for its common use in biomedical applications including in orthopaedic and implantation. HAp can be extracted from natural resources such as eggshells, fish bones and coral. Annually, it is found that huge amount of tuna fish bones was thrown away and being wasted as results from great consumption of tuna fish. In this study, tuna fish bones were extracted and characterised to be used in biomedical applications. Specifically, tuna fish bones were cleaned, and calcined at high temperature of 700 °C, 900 °C and 1100 °C. Powders calcined at 700 °C showed pure HAp compared to powders calcined at 900 °C and 1100 °C which showed the presence of β-TCP. As temperature rising, the morphology of the powders also changes from spherical-shaped to irregular-shaped indicated the substitution of phosphate and calcium from the β-TCP which also influenced the ratio of Ca/P obtained. In this study, powders calcined at 700 °C obtained optimum Ca/P ratio of 1.60. Moreover, EDS analysis showed the presence of tracer elements such as Ca, Mg, Sr Na, K and Zn in all calcined samples. These elements can help improve the biocompatibility of the HAp and beneficial for biomedical applications.